ANALISIS YURIDIS KEDUDUKAN UNDANG-UNDANG PEMBERANTASAN TINDAK PIDANA TERORISME DALAM SISTEM HUKUM PIDANA NASIONAL PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - Lume Hetty Alphani Simbolon; Sumarno; Suci Ramadani; Briski Viktor H. Sinaga; Derta Simbolon; Rika Suryana Surbakti (Berajah Journal, 2026)
The enactment of Law Number 1 of 2023 concerning the Indonesian Criminal Code (National Criminal Code) marks a significant milestone in the reform of Indonesia's criminal law, introducing a new paradigm for sentencing and the national criminal justice system. Meanwhile, terrorism offenses continue to be specifically regulated under Law Number 5 of 2018, which amended Law Number 15 of 2003 on the Eradication of Criminal Acts of Terrorism. This legal framework raises questions regarding the position of this special legislation within the national criminal law system following the implementation of the National Criminal Code. This study aims to analyze the legal status of the Anti-Terrorism Law within Indonesia's national criminal law system and to examine the juridical implications of applying the principle of lex specialis derogat legi generali. The research employs a normative legal research method using statutory, conceptual, and comparative approaches. The data were analyzed qualitatively through library research involving legislation, legal doctrines, and court decisions. The findings indicate that the enactment of the National Criminal Code does not abolish the existence of the Anti-Terrorism Law, as it continues to apply as a special criminal law based on the principle of lex specialis derogat legi generali. Nevertheless, further harmonization is required, particularly concerning the sentencing system, the objectives of punishment, corporate criminal liability, and the protection of human rights, in order to ensure legal certainty and consistency within Indonesia's national criminal law system.